Re-design of Child-Friendly Integrated Public Spaces in Kebon Pala Village - Ulinata, Ulinata; Dianty, Grace Putri; Jourdan, Gabrielle Charles; Indry, Jessica Miracella (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Community Service activities conducted by the UKI’s Architecture Study Program focused on the theme of 'Green Action 35: Redesign of Child-Friendly Integrated Public Space in Kebon Pala Village’. The aim is to provide design proposals to restore its usability and functionality for Child-Friendly Integrated Public Space which has become unsuitable and non-functional. The method involves conducting a location survey, measuring and documenting the existing conditions, and creating a design proposal for the renovation, which will be presented to the Village Head, sub-district officials, and the management of the Child-Friendly Integrated Public Space. The result of this Community Service activity is a design proposal that is expected to be implemented so it can be reused.